The Son of Neptune: The Heroes of Olympus #2 #2 - Riordan, Rick (New York : Disney/Hyperion Books, 2011)
Demigod Percy Jackson, still with no memory, and his new friends from Camp Jupiter, Hazel and Frank, go on a quest to free Death, but their bigger task is to unite the Greek and Roman camps so that the Prophecy of Seven can be fulfilled.
Keywords: Mythology, Roman -- Juvenile fiction; Mythology, Greek -- Juvenile fiction; Hera (Greek deity) -- Fiction; Gaia (Greek deity) -- Fiction; Roman mythology, Roman -- Fiction; Greek mythology -- Fiction; Camps -- Fiction; Hera (Greek deity) -- Fiction; Gaia (Greek deity) -- Fiction; Monsters -- Fiction; Prophecies -- Fiction; Mythology, Roman -- Fiction; Mythology, Greek -- Fiction; Camps -- Fiction; Monsters -- Fiction; Prophecies -- Fiction